Метод выявления и практической реализации баллистического резерва ствольных систем огнестрельного метания в контексте проблемы ресурсосбережения - Нелаев, В. П. (НТУ "ХПИ", 2010)
The method of revealing and practical realization of the gun ballistic reserve is offered. On the example of smoothbore hunting gun effectiveness of the method is shown. The offered method is not restricted by a caliber or gun specific and can be applied to any gun, which ballistic efficiency is explored for the purpose of increase
Keywords: стрелковое оружие; метательный заряд; баллистический резерв; патрон; порох